ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM KONSTRUKSI BUMN DENGAN REGRESI PANEL DINAMIS - Lisa Dwi Ardianti (Quantitative Economics Journal, 2016)
This study aims to determine the factors that affect stock returns in the Indonesian state-owned construction period January 2013 to December 2015. The variables used were trading volume, market capitalization, inflation, exchange rate and government policy. The data in this research is secondary data obtained from the publication of the Central Bureau of Statistics, Ministry of Commerce and the Indonesia Stock Exchange. This study uses a dynamic panel regression by the method of Generalized Method of Moments (GMM). The results showed that lagged stock returns, trading volume at this time and the exchange rate at the moment significant negative effect on stock returns. While the market capitalization in the current and prior periods and inflation at the moment and the two previous period significant positive effect on stock returns. Besides the government's policy affect to state-owned construction stock returns where policies are made in the era of President Joko Widodo more influence smaller than the policy made during the leadership of President Susilo Bambang Yudhoyono.